Short-term effects of 448 kilohertz radiofrequency stimulation on plantar fascia measured by quantitative ultrasound elastography and thermography on active healthy subjects: an open controlled clinical trial - Aguilar-Nuñez, Daniel; Cervera-Garvi, Pablo; Gonzalez-Muñoz, Ana; Navarro-Ledesma, Santiago (International journal of hyperthermia, 2024)
This study is an open clinical trial. The aim of this study was to show the changes that occur in the viscoelastic properties of the plantar fascia (twenty healthy volunteers) measured by SEL and the changes in the plantar fascia temperature measured by thermography after the application of a 448 kHz capacitive resistive monopolar radiofrequency (CRMR) in active healthy subjects immediately after treatment and at the 1-week follow-up. Furthermore, to analyze if an intervention with 448 kHz CRMR in the plantar fascia of the dominant lower limb produces a thermal response in the plantar fascia of the non-dominant lower limb. The final objective was to analyze the level of association between the viscoelastic properties of the PF and the temperature before and after the intervention with 448 kHz CRMR. Our results showed that a temperature change, which was measured by thermography, occurred in the plantar fascia after a single intervention (T0-T1) and at the 1-week follow up (T1-T2). However, no changes were found in the viscoelastic properties of the plantar fascia after the intervention or at the 1-week follow up. This is the first study to investigate changes in both plantar fascia viscoelastic properties and in plantar fascia temperature after a radiofrequency intervention.